Kindergarten in a Large Urban District. (August 2021) - Engel, Mimi; Jacob, Robin; Claessens, Amy; Erickson, Anna
Using data from 82 classroom observations conducted in a large urban school district, we explore how kindergartners spend their time in general and across schools serving children from lower and higher income households. Consistent with prior research, we find that kindergartners spend the majority of instructional time on reading and mathematics, with little time devoted to other subjects. On average, 2.5 hours are spent on noninstructional activities such as transitions. Kindergartners in lower income schools spend more time on reading and mathematics and experience more noninstructional time. They also spend substantially less time being physically active and have fewer opportunities to choose their own activities than their peers in higher income schools.